Assessment of vulnerability in agricultural sector in disaster prone areas of Bangladesh (Bangladesh Journal of Scientific Research, 2016)
A study was carried out in 24 Upazillas of 12 districts of Bangladesh with a view to identifying risks, vulnerabilities and impacts of different types of natural disasters commonly occurring in Bangladesh with respect to agricultural production and sustainable agricultural development. Three districts were selected from each category of the disaster viz., drought, saline, river flood and flash flood prone. Two Upazillas were selected randomly from each district by considering the homogeneity (climate, agricultural practices, agricultural production, disaster risks, livelihood system, population, etc.) of the particular disaster affected areas. Of the four disasters, drought prone area covers the highest net cultivable area (NCA) measuring about 121 ha. Flash flood, salinity and river flood prone area covers approximately 115, 60 and 30 ha, respectively. The dominant cropping pattern in drought areas is Fallow-T.Aman-Wheat. In saline areas, it is Fallow-T. Aman- Pulse while in flood areas, it is Fallow-T.Aman- HYV Boro. Trend analysis shows that overall cropped area decreased by 1% in all disaster prone areas from 1984 - 2013. The highest decrease in cropped area was found for pulse in both drought (13%) and river flood (14%) areas. In saline and flash flood areas, it was for spice and potato, respectively. Among 72 farmers, 85% is vulnerable to drought, 90% to salinity, 69% to river flood and 95% to flash flood. Medium high land was found to be the most vulnerable for agricultural production in all disaster prone areas. Due to vulnerability to disasters, medium high land remains fallow in saline (83%), river flood (51%) and flash flood (31%) areas. In case of drought regions, medium low land (37%) remains fallow.Bangladesh J. Sci. Res. 28(2): 91-101, Dec-2015